Incorporating Root Crops under Agro-Forestry as the Newly Potential Source of Food, Feed and Renewable Energy - Yudi Widodo; St. A. Rahayuningsih; Nasir Saleh; Sri Wahyuningsih (Center of Biomass & Renewable Energy (CBIORE), 2014)
Entering the third millennium food and energy crisis is becoming more serious in line with water scarcity amid of climate change induced by global warming, that so called as FEWS (food energy and water scarcity). In the last five decades Indonesian agricultural development of food crops had been emphasized on cereals and grains based. Conversion of forest into agricultural field in the form of upland and lowland facilitated by irrigation is prioritized for cereals such as rice, maize as well as grain legumes such as soybean, peanut etc. Unfortunately, root crops which their main yield underground are neglected. At the end of second millennium Indonesia was seriously suffered from multi-crisis economic trap, so Indonesia as part of countries under World Food Program to import the huge of food to cover domestic consumption such as rice, wheat, soybean, corn etc. On the other hand, consumption of energy was also increase significantly. These conditions triggering government to stimulate integrated agricultural enterprises for providing abundance of food as well as adequate renewable energy. Although root crops were neglected previously, however from its biological potential to produce biomass promotes root crops into an appropriate position. The variability of root crops which ecologically can be grown from upland in dry areas till swampy submergence condition. Forest conversion into agricultural land is not allowed due to forest is useful to prevent global warming. Therefore, food, feed and fuel (renewable energy) production have to be able grown under agro-forestry. Fortunately the potential of root crops has competency to meet the current need to fulfil food, feed and fuel as well as fibre under future greener environment.